Cervical lacerations in planned versus labor cerclage removal: a systematic review. (October 2015) - Simonazzi, Giuliana; Curti, Alessandra; Bisulli, Maria; Seravalli, Viola; Saccone, Gabriele; Berghella, Vincenzo
Abstract: Objective: The aim of this study was to evaluate the incidence of cervical lacerations with cerclage removal planned before labor compared to after the onset of labor by a systematic review of published studies. Study design: Searches were performed in electronic databases from inception of each database to November 2014. We identified all studies reporting the rate of cervical lacerations and the timing of cerclage removal (either before or after the onset of labor). The primary outcome was the incidence of spontaneous and clinically significant intrapartum cervical lacerations (i.e. lacerations requiring suturing). Results: Six studies, which met the inclusion criteria, were included in the analysis. The overall incidence of cervical lacerations was 8.9% (32/359). There were 23/280 (6.4%) cervical lacerations in the planned removal group, and 9/79 (11.4%) in the removal after labor group (odds ratio 0.70, 95% confidence interval 0.31–1.57). Conclusions: In summary, planned removal of cerclage before labor was not shown to be associated with statistically significant reduction in the incidence of cervical lacerations. However, since that our data probably did not reach statistical significance because of a type II error, further studies are needed.